Advances in transfusion science for shock-trauma: Optimising the clinical management of acute haemorrhage. Issue 3 (December 2015) - Seghatchian, Jerard; Putter, Jeffrey S.
Abstract: The primary resuscitation of severely injured patients, acute haemorrhage and shock-trauma has been well reported in the literature. Resuscitation protocols include the use of diverse agents such as fresh whole blood [FWB], packed red blood cells [PRBCs], reconstituted blood products, fresh frozen plasma [FFP] and its derivative concentrates or recombinant products, volume expanders and tranexamic acid [TXA]. The reasonably prudent use of these agents and products is necessary to reverse risk factors of haemorrhagic shock such as haemodilution, hypothermia, acidosis and coagulopathy. Addressing the mechanisms of haemoregulation in the pathophysiology of DIC is important to optimise transfusion practice.